Development of educational courses on space science technology in Nepal - Adhikary, Krishna Raj (Journal on Geoinformatics, Nepal, 2009)
Space science and Geomatics education in Nepal is recently started on some of the training institution and university of Nepal. Preliminary subjects required for space science and technology have been introduced into science curricula at the higher secondary level of the Nepalese’s school, however the benefit of space science and technology have not been appreciated enough. Facilities and resources of teaching science and technology at educational institutions are not yet developed. Attempts have been made to incorporate the elements of space science and technology into undergraduate level of education of the university. This paper starts with the discussion on the space science education in Nepal at the school and college level and mainly focus on initiation taken by the training institution and university of Nepal to introduce the subjects of space science and technology at their curriculum on geomatics engineering and other engineering education. Some recommendation have been made to introduce the different type of educational courses and/or training on space science and technology, which will meet the needs of development to built a general capability in space science as a necessary support for infrastructure development of Nepal and consequently will help to promote the educational activities on space science education in the country.